Electrochemistry Study of Permselectivity and Interfacial Electron Transfers of a Branch-Tailed Fluorosurfactant Self-Assembled Monolayer on Gold - Shanshan Li (Molecules, 2018)
We investigated the permselectivity and interfacial electron transfers of an amphiphilic branch-tailed fluorosurfactant self-assembled monolayer (FS-SAM) on a gold electrode by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The FS-SAM was prepared by a self-assembly technique and a “click„ reaction. The barrier property and interfacial electron transfers of the FS-SAM were also evaluated using various probes with different features. The FS-SAM allowed a higher degree of permeation by small hydrophilic (Cl− and F−) electrolyte ions than large hydrophobic (ClO4− and PF6−) ones. Meanwhile, the redox reaction of the Fe(CN)63− couple was nearly completely blocked by the FS-SAM, whereas the electron transfer of Ru(NH3)63+ was easier than that of Fe(CN)63−, which may be due to the underlying tunneling mechanism. For hydrophobic dopamine, the hydrophobic bonding between the FS-SAM exterior fluoroalkyl moieties and the hydrophobic probes, as well as the hydration resistance from the interior hydration shell around the oligo (ethylene glycol) moieties, hindered the transport of hydrophobic probes into the FS-SAM. These results may have profound implications for understanding the permselectivity and electron transfers of amphiphilic surfaces consisting of molecules containing aromatic groups and branch-tailed fluorosurfactants in their structures.